STRATEGI PEMENANGAN CALON DALAM PEMILIHAN UMUM LEGISLATIF TAHUN 2014 MELALUI JARINGAN CEKIAN DI BALI - Prasetya, I Gede Ngurah Aris; Noak, Piers Andreas; Erviantono, Tedy (Jurnal Nawala Politika, 2016)
ABSTRACT In achieving power through political channels, the network becomes a factor decisive victory of candidates, the establishment of the network through the tournament ceki seen will be able to influence voting results candidates. This research was conducted in Denpasar, Singaraja and Jembrana and examines the development of the network through the game entrenched in society that ceki game. Powercube theory or the theory that describes the power cube in three dimensions, namely levels, space and form. Associated with the tournament ceki, the initiator who is chairman of the political parties that are in the first dimension that has stratified the top, the second dimension is the space where the tournament as a party to organize and coordinate with the community and participants, the third dimension dimensional shapes, participants ceki and volunteers become abgian the third dimension is either in open or closed. Qualitative Descriptive deemed appropriate peel this issue because it will be able to clarify the phenomena that occur in the community post-implementation ceki tournament. Political participation ceki participants showed a positive effect after the holding of the tournament ceki, they assume that their candidate has been championing the aspirations . Keywords: sekaa ceki, tournament ceki, political participation